2021
DOI: 10.1002/jor.25209
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and microstructural organization of common ulnar collateral ligament grafts: Palmaris longus and gracilis tendons

Abstract: Ulnar collateral ligament (UCL) injuries are becoming increasingly common. The palmaris longus (PL) and gracilis (GR) tendons are the most common grafts used in UCL reconstructions. While clinical studies have demonstrated relatively similar outcomes for either graft, there is little quantitative data describing these grafts from a material perspective, specifically the mechanical and microstructural properties of these tissues and how they respond under dynamic loading. The purpose of this descriptive laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…2 Stress-strain graph of one of the kMCL samples depicting outcomes measures analyzed, including: toe region Young's modulus (slope of the toe region line), linear region Young's modulus (slope of the linear region line), yield stress, maximum stress, and maximum toughness (the area under the curve) to increase with increasing strain for tendons [6,9-11 16]. The strain used in the present study was 5%, which demonstrated a similar decrease in stress compared to previous findings for both PL and kMCL [6,28].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…2 Stress-strain graph of one of the kMCL samples depicting outcomes measures analyzed, including: toe region Young's modulus (slope of the toe region line), linear region Young's modulus (slope of the linear region line), yield stress, maximum stress, and maximum toughness (the area under the curve) to increase with increasing strain for tendons [6,9-11 16]. The strain used in the present study was 5%, which demonstrated a similar decrease in stress compared to previous findings for both PL and kMCL [6,28].…”
Section: Discussionsupporting
confidence: 74%
“…From this sample, a 5 × 50 mm measured section was dissected from the mid-substance of the tendon. Previous research has demonstrated there is no significant difference in the material properties of the distal, proximal, and middle sections of the PL tendon [28].…”
Section: Tissue Preparationmentioning
confidence: 79%
See 1 more Smart Citation
“…33,34 In contrast, recent microstructural and mechanical characterization of the palmaris graft showed that it had an increased modulus, a higher baseline strength of fiber alignment, and greater change in fiber alignment during tensile loading compared with the native UCL. 36 It is possible that the addition of the suture tape in the augmented reconstruction could offer an additional checkrein to share the load and deformation on the palmaris graft, resulting in a lessened potential dynamic realignment and greater similarity of native collagen architecture dynamics to the native UCL. Future studies examining changes in dynamic collagen realignment with and without suture tape could investigate this potential advantage of the augmented reconstruction procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic changes in microstructural organization can be recorded and analyzed via the creation of collagen fiber alignment maps (Figure 2D) (Quinn and Winkelstein, 2008;Lake et al, 2010;Buckley et al, 2013;Skelley et al, 2015;Shah et al, 2016;Zhang et al, 2016;Barnum et al, 2017;Wu et al, 2018;Smith et al, 2019). These spatial maps of collagen organization then can be correlated with tissue microstructural and mechanical properties to link structure-function relationships (Skelley et al, 2015;Skelley et al, 2016;Wright et al, 2016;Smith et al, 2019;Solon et al, 2021).…”
Section: Polarization Imaging and Microscopymentioning
confidence: 99%